2004
DOI: 10.1001/archotol.130.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Regression of HPV-Positive Tumors Treated With a New Listeria monocytogenes Vaccine

Abstract: Background: Human papillomavirus (HPV) has been implicated in the pathogenesis of 15% to 23% of head and neck squamous cell carcinomas as well as most oropharyngeal carcinomas. The viral oncoproteins E6 and E7 are expressed in HPV-positive tumor cells and therefore provide ideal targets for tumor immunotherapy. Because of its unique ability to induce a cellular immune response, the intracellular bacteria Listeria monocytogenes has been studied as a potential HPV-positive tumor vaccine. Objective: To present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…Recombinant L. monocytogenes vaccines that express tumor antigens have been shown to lead to the generation of tumor-specific T-lymphocytes and tumor regression in mouse models (1)(2)(3)(4)(5). In the present study, we have determined that the fusion of the antigen to a PEST sequence is critical for the efficacy of these vaccines.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recombinant L. monocytogenes vaccines that express tumor antigens have been shown to lead to the generation of tumor-specific T-lymphocytes and tumor regression in mouse models (1)(2)(3)(4)(5). In the present study, we have determined that the fusion of the antigen to a PEST sequence is critical for the efficacy of these vaccines.…”
Section: Discussionmentioning
confidence: 89%
“…Once in the cytoplasm, bacterial proteins are effectively presented to cytotoxic T lymphocytes, thus initiating a cellular immune response against bacterial antigens. By engineering recombinant Listeria vaccines to secrete not only bacterial antigens but also tumor antigens, immune responses have been generated sufficient to cause the regression of established tumors in animal models (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The adjuvant properties of LLO have been demonstrated not only in the context of L. monocytogenes (17) but also in various vaccine platforms, such as modified vaccinia virus Ankara (MVA) or plasmid DNA (pDNA), and as a protein carrier for anti-idiotypic immune therapy of non-Hodgkin's lymphoma (12,13,(17)(18)(19)(20), suggesting broad applicability in immunotherapeutic strategies. Although there are sufficient data supporting LLO as a potent immune activator, how it exerts these effects is unknown.…”
mentioning
confidence: 99%
“…We thus engineered a recombinant strain of Listeria monocytogenes to express and secrete HPV-16 E7 as a fusion protein with ActA. Studies assessing the ability of this vaccine strain of Listeria revealed complete regression of established, E7-expressing TC-1 tumors in C57BL/6 mice while inducing E7-specific cytotoxic T-lymphocyte activity [30].…”
Section: Listeria Monocytogenes As a Vector For Human Tumor Antigensmentioning
confidence: 99%